Galaxy Internet Center (GIC) / Thomas Anak Baos ... [et.al.]. - Baos, Thomas; Lanchang, Kereen Samban; Sulainan, Sheril Nur Haziani (2018)
Galaxy Internet Center is our company name which provide internet service, printing and scanning services, and also provide It classes for community. Our company want to introduce our internet center concept plus provide printing service and tutor service to the people especially to Desa Ilmu area.